2021
DOI: 10.21203/rs.3.rs-249948/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Prevalence and correlates of major injuries among older adults in India: Results of a national cross-sectional survey in 2017-2018

Abstract: Background: The study aimed to examine the prevalence and correlates of injury among older adults in India. Methods: The study included 72,262 individuals (45 years and older) from the cross-sectional 2017-2018 Longitudinal Ageing Study in India (LASI) Wave 1.Results: More than one in ten participants (12.9%) had a major injury in the past 2 years, 2.3% had a road traffic injury, 9.4% had a fall injury and 1.9% had other injuries in the past 2 years. In adjusted logistic regression analysis, having 5-9 years e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Sleep latency of more than 20 minutes falls under the category of insomnia. In a large (n=72,262) pre-pandemic study conducted in India, Pengpid et al ( 2021) [22] found the prevalence of insomnia to be 12.7% among adults. Certainly, the problem has increased during the pandemic.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sleep latency of more than 20 minutes falls under the category of insomnia. In a large (n=72,262) pre-pandemic study conducted in India, Pengpid et al ( 2021) [22] found the prevalence of insomnia to be 12.7% among adults. Certainly, the problem has increased during the pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, those with a BMI of more than 25 had a slightly higher prevalence of disturbed sleep compared to those with a BMI of less than 25, but this was not statistically significant. Studies in the past have linked disturbed sleep to higher BMI, being overweight, or being obese [22].…”
Section: Discussionmentioning
confidence: 99%